Linking farmers' management decision, demographic characteristics and perceptions of ecosystem services in the Southern Pampa of Argentina - De Rito, Mara Victoria (2020)
In the Pampean region of Argentina, uncultivated areas with spontaneous vegetation, such as the sierras (low hills), are important sites for nature conservation. In the last decades, the “agriculturization” process has generated different pressures on these areas and their fate depends on farmers' decision making. In order to understand the context of these decisions, it is important to know the farmers' demographic characteristics and perceptions of ecosystem services (ES). The aim of this study was to explore the link between farmers' management decisions and their demographic characteristics and perceptions of ES in one of the most intensively cropped areas in Argentina. Data were obtained from 40 semi-structured interviews with farmers from the Tandilia system in the Pampean region. A typology of farms was generated according to their management practices and then characterized by the farmers' demographic characteristics and perceptions of ES. The results show a typology of four groups of farms defined by the combination of eight management variables. The demographic characteristics of the farmers that have a strong perception of ES derived from the sierras were related to an emotionally and/or physically close connection with the farm (their parents were farmers, they were raised on the farm, they have worked there for many years, the farm is their place of residence, and it is a family farm). However, neither the farmers' demographic characteristics nor their perceptions of ES were related to their management decisions. This is explained by the fact that the agricultural model that characterizes the region generates different pressures on farmers and leaves them with little choice in the matter of productive management decisions. The information derived from this work could contribute to the design of guidance criteria for sound environmental management strategies and policy instruments for the conservation of biodiversity and the provision of ES in a context with particular ecological, social, and economic characteristics.